The problem of valuation of state-owned real estate in the Republic of Moldova - Albu, Svetlana; Albu, Ion (Technium Social Sciences Journal, 2022)
This study examines the issues that arise at the stage of implementation of the enforcement acts on the capitalization of public property in the public domain, especially those faced by real estate appraisers. Conceptual and defining legislative errors are exemplified and analyzed. The authors proposed some solutions in order to harmonize the legislative aspects with the executive ones related to the public patrimony, in particular the correlation of the provisions of the regulation regarding the capitalization of the state-owned lands with the regulations of the evaluation activity in the Republic of Moldova.